Technology applied to a particular case of multiple disability - Patiño-Cuervo, Oliva; Caro, Edgar Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The results of a study called: communicator for children with multiple disabilities and its effect on the manifestation of a basic need, are shown. The study was developed with the objective of interpreting the behavior of a three year old child with visual impairment and autism, in the communication of his desire to feed, mediated by a communicator adapted to his individual characteristics.  The booklet includes the approach of the communicator as a facilitator in the acquisition of oral language, under a 30 day intervention, six hours a day. The results of the process are presented in different theoretical-methodological moments, from an approximation to the case study in its specific peculiarities, which after having been analyzed, led to the construction of a type of Alternative and Increasing communication System, which coupled with a process of mediation; allowed us to validate the Feuerstian notion of Cognitive Structural Modifiability.